Are Emotions Universal or Culturally Shaped? - Rona Utami (Digital Press Social Sciences and Humanities)
Emotions are not just personal feelings, they are also shaped by the cultures and values we live in. This article explores the question: Are emotions the same everywhere, or do different societies feel and understand emotions differently? Using a philosophical approach, the article argues that emotions are more than biological reactions. They are ways of making sense of the world, shaped by language, tradition, and ethical beliefs. Emotions help us understand what matters, what is right or wrong, and how we relate to others. Focusing on Indonesian emotional concepts such as malu (shame), sungkan (respectful hesitation), and sakit hati(emotional pain), the article shows that emotions are part of moral life. These feelings guide behavior in families, communities, and society. They are not only about what someone feels inside, but also about shared expectations and values. The article compares these with ideas from Western philosophy, such as guilt, pride, and compassion, to show how different cultures express and understand emotions in unique ways. Rather than seeing emotional differences as a problem, the article argues that they can help us grow in understanding and empathy. Recognizing emotional diversity is important for building respectful relationships between cultures. The article concludes that emotions are ethical practices that shape who we are and how we live with others. By paying attention to how emotions work across cultures, we can create a deeper, more humane understanding of what it means to live well in a global world. This research concludes that understanding the plurality of emotional expressions and cultivating emotional awareness is essential for intercultural harmony and mutual respect